Who gains from trade protection in Ghana: A household-level analysis? - Charles Ackah; Oliver Morrissey; Simon Appleton (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2007)
In this paper, we present one of the first direct microeconometric studies of the impact of trade protection on household income in Ghana. Tariff measures at the two-digit ISIC level are matched to Ghanaian household survey data for 1991/92 and 1998/99 to represent the tariff for the industry in which the household head is employed. We examine the possibility that the effect of protection on income might not be uniform across households characterized by different skill levels. Specifically, we allow the relationship between welfare and trade policy to differ for households with different levels of education. In the absence of suitable panel data, the analysis applies pseudopanel econometric techniques to our repeated cross-section data. This method has rarely been used in poverty analysis. The results suggest that higher tariffs are associated with higher incomes for households employed in the sector, so tariff reductions may reduce incomes (and increase poverty), at least in the short run, but with differing effects across skill groups. We find that this positive effect of protection is disproportionately greater for low skilled labour households, suggesting an erosion of welfare of unskilled labour households would result from trade liberalization. We conclude that contemplating trade liberalization without recognizing the complementary role of human capital investment may be a sub-optimal policy for the poor, at least in the short-run.
Keywords: F14; J31; O12; O55; 330; Tariffs; Trade liberalisation; Household welfare; Pseudo-panel; Ghana; Protektionismus; Zoll; Haushaltseinkommen; Schätzung; Ghana